ADAPTING TO DIGITAL PEDAGOGY: LECTURERS’ EXPERIENCES IN INTEGRATING ICT TOOLS AT UNIVERSITAS MUHAMMADIYAH PALEMBANG - Tanti Nur Annisa; Adhadilah Galuh Andaresta; Masagus Firdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Study explores lecturers’ experiences in adapting to digital pedagogy through the integration of Information and Communication Technology (ICT) tools at Universitas Muhammadiyah Palembang. Using a qualitative approach, data were collected through semi-structured interviews and classroom observations. The findings reveal that ICT integration has reshaped lecturers’ teaching practices, encouraging more interactive, flexible, and student-centered learning environments. However, challenges such as limited institutional support, technological infrastructure, and lecturers’ digital competence remain significant barriers. This study highlights the need for continuous professional development and strategic policies to strengthen digital pedagogy implementation in higher education.